The image of the General Entertainment Authority among a sample of male and female students at King Abdulaziz University - Alotaibi, Rahaf Hmeed; Bendenia, Fatima kobibi (Arab Journal for Sciences and Research Publishing, 2025)
The current study aimed to explore the public image of the General Entertainment Authority (GEA) among a sample of students at King Abdulaziz University, focusing on the cognitive, emotional, and behavioral dimensions, as well as identifying the sources shaping this image. The study adopted a descriptive analytical approach, utilizing an electronic questionnaire to collect data from a random sample of 385 students. The key findings revealed that most participants agreed on the presence of a strong cognitive dimension of the GEA’s image, with a mean score of 4.59, indicating a high level of awareness regarding its activities and roles. The emotional dimension was also significant, with a mean score of 4.45, as most respondents expressed positive feelings toward the GEA. Social media emerged as the primary source for shaping the GEA’s image (mean score: 4.26), highlighting the impact of digital content on public perception. Conversely, press reports had the least influence, with a mean score of 3.89. Finally, the study recommends enhancing communication channels with the public, organizing activities that consider gender and age diversity, and launching awareness campaigns through both traditional and modern media to clarify the GEA’s mission and objectives.
Keywords: Image; General Entertainment Authority; King Abdul-Aziz University